Dalit women as victims: iconographies of suffering, sympathy and subservience. Issue 1 (2nd January 2016) - Gupta, Charu
ABSTRACT: This article explores how, in a section of upper-caste reformist writings in Hindi, in colonial north India, Dalit women came to be dominantly represented as victims. Images of the permanently polluted, evil and grotesque Dalit woman's body gave way to images of her suffering body, which came together in iconographies of sentimentality, sympathy and subservience. This shift in representation of Dalit women – from polluting to victimised, and lascivious to vulnerable – was symbolised by the reallocation of focus from Surpanakha to Shabari. The article shows how such a move allowed for a conceptualisation of an ideal Dalit woman, embodying deference and obedience, as reformers and nationalists faced the challenge of transforming stigmatised bodies into suffering Hindus. It also provided them with a stamp of historical legitimation. At the same time, the article argues, there were various limits to such sentimentality, inextricably bound as it was within limited frameworks of charitable benevolence and spectatorial pity, where Dalit women appeared as mute sufferers and romanticised submissive beings. The move towards liberal sympathy, while attempting to reclaim 'untouchables' within a putative Hindu community and nation, privileged a language of personal and domestic betterment from within. The article underscores how such idioms were often invoked evading questions of structural inequalities, and focuses on the limits and ambiguities of social reform vis-à-vis caste and gender.